K06 Psychosis in HD: a data mining study from REGISTRY. (29th August 2012) - Crooks, J; Rickards, H; ,
Abstract : Background: There is little consensus in the literature surrounding the prevalence and incidence of psychotic symptoms in Huntington's Disease (HD) with prevalence rates varying from 5% to 64%. The differences may be due to the sample population used and/or that many of the negative symptoms of schizophrenia such as flat affect, poor social functioning and apathy are commonly observed symptoms of HD. Aim: To demonstrate prevalence and incidence rates of psychotic symptoms within the REGISTRY data. To identifying differences in presentation between those who report psychosis and those who do not. Method: Participants were regarded as reporting psychosis if they scored >1 on the delusion and/or hallucination items of the UHDRS Behaviour Scale. For those who did not report psychosis the first completed data set was used, whereas those who reported psychosis, the first data set mentioning psychotic symptoms was included. Data sets for 998 participants (1597 visits) were used (497 female, 501 male). Results: Prevalence of psychosis (n 65) as defined above was 6.51 %. Delusions (n 43) were most prevalent (4.31%). A further 39 participants reported a previous history of psychosis which equates to an overall lifetime prevalence of 10.42%. Incidence was 2.84 new reports of psychotic symptoms per hundred per year. Those with psychosis are generally more seriously affected with HD, with higher motor score, and lower TFC, function, and cognitive UHDRS scores. Those people reporting psychotic symptoms are more likely to have a previous psychiatric history, to initially present with psychiatric symptoms and have other behavioural problems. Summary: Reports of psychotic symptoms are lower than previously reported. However further research is needed to validate the UHDRS behaviour items used to measure delusions and hallucinations before drawing conclusions from this data.